2019
DOI: 10.1016/j.jseaes.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Triassic vegetation and climate evolution on the northern margin of Gondwana: a palynological study from Tulong, southern Xizang (Tibet), China

Abstract: We present vegetation reconstructions based on an almost complete succession through the Triassic of Tulong, Nyalam County, southern Xizang (Tibet), China. The Permian and earliest Triassic samples were barren of palynomorphs, however, in overlying strata we identified well-preserved and diverse miospore assemblages. Seven pollen and spore zones spanning the Olenekian to the Rhaetian were recognized. These palynological zones were amalgamated into three floral stages that comprise distinct vegetation types: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Early Olenekian palynofloras, similar to the ones described here, were reported by Schneebeli-Hermann et al (2012) and Peng et al (2019) from the Tulong area in South Tibet (Figures 5 and 6). The early Olenekian assemblages are characterized by Densoisporites spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Early Olenekian palynofloras, similar to the ones described here, were reported by Schneebeli-Hermann et al (2012) and Peng et al (2019) from the Tulong area in South Tibet (Figures 5 and 6). The early Olenekian assemblages are characterized by Densoisporites spp.…”
Section: Discussionsupporting
confidence: 89%
“…The late Olenekian palynoflora is dominated by bisaccate pollen including Lunatisporites pellucidus , L. noviaulensis ,? Crustaesporites sp., and Alisporites / Falcisporites spp., and a diversification of the Aratrisporites group is recognized (Peng et al 2019). Liu et al (2020) also analyzed palynofloras in the same area and defined the Lundbladispora brevicula-Densoisporites nejburgii (BN) assemblages considered coeval with those mentioned above, and the succeeding Falcisporites nuthallensis-Alisporites landianus (NL) is distinguished by the increase of pollen grains and the occurrence of R. catenatulus .…”
Section: Discussionmentioning
confidence: 99%
“…These size variations in S. quadrifidus are potentially the result of intraspecific variation and/or differences in pollen maturity (Baranyi et al 2018). Seven specimens from southern Xizang, China (Peng et al 2018a(Peng et al , 2019 were identified as Staurosaccites; of which, six (Figure 1Q-V) are assigned to S. quadrifidus based on the absence of a differentiated saccus exoexine and a clear corpus outline.…”
Section: Systematic Palynologymentioning
confidence: 99%
“…Occurrence and age. -Carnarvon Basin, Western Australia (Dolby & Balme 1976), Pelsonian (the third substage of Anisian) to early Norian (Nicoll & Foster 1994; Noe Fatu Section in west Timor, Carnian (Martini et al 2000); Tiki Formation, South Rewa Gondwana Basin, India (Kumaran & Maheshwari 1980), Carnian to Norian (Maheshwari & Kumaran 1979); Rajmahal Basin, Bihar, India, Early Norian (Tripathi et al 1990); Ischigualasto-Villa Unión Basin, Argentina (Césari & Colombi 2016), late Carnian (Rogers et al 1993;Martínez et al 2011); Luwegu Basin, Tanzania, Carnian to Norian (Hankel 1987); Laibuxi and Dashalong formations, Tulong Section, southern Xizang, southwestern China (Peng et al 2018a(Peng et al , 2019, late Anisian to early Norian (Wang & He 1976;; Huai Hin Lat Formation, NE Thailand, Norian (Racey et al 1996); Al Azizia Section, northwestern Libya, Ladinian (Mut-toni et al 2001); Kurrachine Dolomite Formation, Palmyrides, Syria, Ladinian (Lučić et al 2010); Prati di Stuores section, northern Italy, Ladinian to Carnian (Broglio Loriga et al 1999;Mietto et al 2012); Mufara Formation, Sicily, late Ladinian to Carnian (Buratti & Carrillat 2002); Pyreenes, Spain, Carnian (Calvet et al 1993); Bjǿrnǿya area, Ladinian to Carnian (Mǿrk et al 1990;Hounslow et al 2007).…”
Section: Systematic Palynologymentioning
confidence: 99%